2005
DOI: 10.1021/bi051030n
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Ligand Binding Domain of the Fibroblast Growth Factor Receptor:  Role of Heparin in the Activation of the Receptor,

Abstract: The three-dimensional solution structure of the ligand binding D2 domain of the fibroblast growth factor receptor (FGFR) is determined using multidimensional NMR techniques. The atomic root-mean-square distribution for the backbone atoms in the structured region is 0.64 A. Secondary structural elements in the D2 domain include 11 beta-strands arranged antiparallely into two layers of beta-sheets. The structure of the D2 domain is characterized by the presence of a short flexible helix that protrudes out of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Crystal structures of several FGF⅐FGFR complexes have established that both D2 and D3 are needed for FGF binding (8). In contrast to the well resolved Ig domains D1 (64) and D2 (60,65), the D3 domain of all investigated FGFR (FGFR1/2/4) constructs (D1D2D3, D2D3, and D3) lead to line broadening beyond detection in solution. The structural integrity of the investigated D3 domain was confirmed by x-ray analysis (successful crystallization of FGFR2 D2D3⅐FGF1).…”
Section: Nmr Studies Indicate a Symmetric Fgf⅐fgfr Dimerization Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal structures of several FGF⅐FGFR complexes have established that both D2 and D3 are needed for FGF binding (8). In contrast to the well resolved Ig domains D1 (64) and D2 (60,65), the D3 domain of all investigated FGFR (FGFR1/2/4) constructs (D1D2D3, D2D3, and D3) lead to line broadening beyond detection in solution. The structural integrity of the investigated D3 domain was confirmed by x-ray analysis (successful crystallization of FGFR2 D2D3⅐FGF1).…”
Section: Nmr Studies Indicate a Symmetric Fgf⅐fgfr Dimerization Modelmentioning
confidence: 99%
“…This observation suggests that, although D2 alone is not sufficient for high affinity FGF binding by itself, the presence of heparin increases the binding affinity of FGF to D2. Indeed a pervious ITC study has shown that the presence of sucrose octasulfate, a heparin analog, enhances binding of FGFR2 D2 to FGFR1 (60).…”
Section: Nmr Studies Indicate a Symmetric Fgf⅐fgfr Dimerization Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ischemia caused by femoral arterial extraction induces the production and release of bFGF, vascular growth factor and platelet-derived growth factor, 34,35 it is likely that heparin potentiates the angiogenic effects of these endogenous growth factors. [16][17][18][19][20][21]36,37 Because the half-life of intravenously administrated heparin is short, that is, 90 min, in the present study, we used heparin calcium that has a longer half-life. 33 The dose of heparin calcium used in the present study was approximately 400 U/kg, which was determined based on the data of previous studies (250-300 U/kg for rats, 14 300 U/kg for humans 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 Heparin treatment has been reported to accelerate neovascularization in a variety of experimental models including those of hindlimb ischemia. [12][13][14][15] Although the precise beneficial mechanisms of heparin treatment have not been completely clarified, the interaction of heparin, endogenous bFGF, [16][17][18][19] and hepatocyte growth factor 20,21 has been proposed.…”
mentioning
confidence: 99%